7q21-rs6964587 and breast cancer risk: an extended case-control study by the Breast Cancer Association Consortium - Milne, Roger L.; Lorenzo Bermejo, Justo; Burwinkel, Barbara; Frank, Bernd; Heil, Jörg; Chang-Claude, Jenny; Hamann, Ute (Journal of medical genetics, 2011)
Background: Using the Breast Cancer Association Consortium, the authors previously reported that the single nucleotide polymorphism 7q21-rs6964587 (AKAP9-M463I) is associated with breast cancer risk. The authors have now assessed this association more comprehensively using 16 independent case-control studies. - Methods: The authors genotyped 14 843 invasive case patients and 19 852 control subjects with white European ancestry and 2595 invasive case patients and 2192 control subjects with Asian ancestry. ORs were estimated by logistic regression, adjusted for study. Heterogeneity in ORs was assessed by fitting interaction terms or by subclassifying case patients and applying polytomous logistic regression. - Results: For white European women, the minor T allele of 7q21-rs6964587 was associated with breast cancer risk under a recessive model (OR 1.07, 95% CI 1.00 to 1.13, p=0.04). Results were inconclusive for Asian women. From a combined analysis of 24 154 case patients and 33 376 control subjects of white European ancestry from the present and previous series, the best-fitting model was recessive, with an estimated OR of 1.08 (95% CI 1.03 to 1.13, p=0.001). The OR was greater at younger ages (p trend=0.01). - Conclusion: This may be the first common susceptibility allele for breast cancer to be identified with a recessive mode of inheritance.
Gesehen am 07.09.2022